2011
DOI: 10.1051/0004-6361/201015912
|View full text |Cite
|
Sign up to set email alerts
|

Neutral and ionized emission lines in the type II Cepheid W Virginis

Abstract: Aims. The aim of this work was to perform a multiphase spectroscopic study of W Vir which represents stars of the class of population II Cepheids, in order to trace the behaviour of emission features in different lines, and to use the data to describe the dynamical processes in the atmosphere of this star associated with the shock wave propagation. Methods. Our spectroscopic study of W Vir involved 18 high-resolution spectra obtained with the help of 3.5-m telescope of Apache Point Observatory. These spectra c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…Once again, they are very similar to those presented for W Vir by Lèbre & Gillet (1992, their Fig. 6) and by Kovtyukh et al (2011, their Figs. 4,8).…”
Section: Emission In Hαsupporting
confidence: 90%
See 4 more Smart Citations
“…Once again, they are very similar to those presented for W Vir by Lèbre & Gillet (1992, their Fig. 6) and by Kovtyukh et al (2011, their Figs. 4,8).…”
Section: Emission In Hαsupporting
confidence: 90%
“…Lèbre & Gillet (1992) used high resolution spectroscopy to follow the evolution of the emission profile of Hα through an entire cycle of W Vir and further improved the shock model. Finally, Kovtyukh et al (2011) extended this study to many metallic lines including Fe I, Fe II, Na I, and Ba II and concluded that W Vir consists in its inner part of a pulsating star with periodic shocks reaching the upper atmosphere and in its outer part of a circumstellar envelope.…”
Section: Emission In Hαmentioning
confidence: 84%
See 3 more Smart Citations